2006
DOI: 10.1002/jcp.20811
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent effects of fatty acids on skeletal muscle metabolism

Abstract: Increased plasma levels of free fatty acids (FFA) occur in states of insulin resistance such as type 2 diabetes mellitus, obesity, and metabolic syndrome. These high levels of plasma FFA seem to play an important role for the development of insulin resistance but the mechanisms involved are not known. We demonstrated that acute exposure to FFA (1 h) in rat incubated skeletal muscle leads to an increase in the insulin-stimulated glycogen synthesis and glucose oxidation. In conditions of prolonged exposure to FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 130 publications
(148 reference statements)
1
54
0
5
Order By: Relevance
“…Dessa forma, a UCP-3 protege as mitocôndrias contra o acúmulo de AG na matriz. Essa hipótese é suportada pelas observações de que a UCP-3 é up-regulada em situações em que a disponibilidade de AG excede sua capacidade de oxidação, incluindo jejum, dieta hiperlipídica, tratamento com hormônios tireoidianos e exercício físico agudo, ao passo que a UCP-3 é down--regulada em situações nas quais a capacidade de oxidar AG é aumentada incluindo treinamento aeróbio e redução da massa corporal (43). Em adição, a expressão elevada de UCP-3 em músculos do tipo II, comparado a músculo do tipo I, é consistente com essa hipótese, uma vez que esse tipo de músculo apresenta baixa capacidade de oxidar lipídios (44).…”
Section: As Eros Como Reguladoras Do Metabolismo De Glicose Durante Aunclassified
“…Dessa forma, a UCP-3 protege as mitocôndrias contra o acúmulo de AG na matriz. Essa hipótese é suportada pelas observações de que a UCP-3 é up-regulada em situações em que a disponibilidade de AG excede sua capacidade de oxidação, incluindo jejum, dieta hiperlipídica, tratamento com hormônios tireoidianos e exercício físico agudo, ao passo que a UCP-3 é down--regulada em situações nas quais a capacidade de oxidar AG é aumentada incluindo treinamento aeróbio e redução da massa corporal (43). Em adição, a expressão elevada de UCP-3 em músculos do tipo II, comparado a músculo do tipo I, é consistente com essa hipótese, uma vez que esse tipo de músculo apresenta baixa capacidade de oxidar lipídios (44).…”
Section: As Eros Como Reguladoras Do Metabolismo De Glicose Durante Aunclassified
“…Insulin resistance, defined as a diminished ability of cells, such as adipocytes, skeletal muscle cells, and hepatocytes, to respond to the action of insulin, plays a central role in the development of several metabolic abnormalities and diseases, such as obesity, type 2 diabetes, and the metabolic syndrome (2,3).…”
mentioning
confidence: 99%
“…It has been suggested that increased reactive oxygen species (ROS) 3 levels are an important trigger for insulin resistance (7). Enhanced ROS production can lead to abnormal changes in intracellular signaling and development of insulin resistance (8).…”
mentioning
confidence: 99%
“…Insulin resistance, defined as a diminished ability of cells, such as adipocytes, skeletal muscle cells, and hepatocytes, to respond to the action of insulin, plays a central role in the development of several metabolic abnormalities and diseases, such as obesity, type 2 diabetes, and the metabolic syndrome (1,2). Decreased glycogen levels are the hallmark of insulin resistance in the hepatocytes.…”
mentioning
confidence: 99%